ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES AS CONSEQUENCES OF ENDOTHELIITIS AFTER COVID-19 - Bobokulova, Sh.A.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Background. Purulent-destructive lung diseases remain a priority among the causes of generalized infec- tion and death. The key to the progression of infection in acute lung abscesses may be associated with impaired barrier-filtration function of this organ, which is based on endothelial dysfunction. Purpose. To determine the role and place of nitroxidergic regulation of the endothelial system in the patho- genesis of acute lung abscess. Methods. The experiments were carried out on 32 Chinchilla rabbits, in which the model of acute lung ab- scess was reproduced. Investigated in blood samples at the entrance and exit from the lungs, such indica- tors as nitrates, nitrites, peroxynitrite, NO-synthase and von Willebrand factor. Results. Nitric oxide produced because of iNOS activation is intended for non-specific protection of the body against a wide range of pathogenic agents, inhibits platelet aggregation and improves local blood cir- culation. However, these changes do not occur. The main role in this direction is assigned to peroxynitrite, which, due to its pathogenicity, worsens the already process associated with endothelial dysfunction. Conclusion. The nature of the changes in the parameters of the nitroxidergic regulation of the endothelial system in the lungs has a staging: compensated and decompensated. All this is of a natural nature, based on certain relationships between the indicators of the nitroxidergic regulation system.